The complete mitochondrial genome of Malayan Gaur (Bos gaurus hubbacki) from Peninsular Malaysia. Issue 2 (3rd July 2019) - Rosli, Norsyamimi; Sitam, Frankie Thomas; Rovie-Ryan, Jeffrine Japning; Gan, Han Ming; Lee, Yin Peng; Hartini Ithnin; Millawati Gani; Mohd Firdaus Ariff Abdul Razak; Md-Zain, Badrul Munir; Abdullah, Mohd Tajuddin
Abstract: Here, we present the first complete mitochondrial genome of Malayan Gaur ( Bos gaurus hubbacki ) inferred using next-generation sequencing. The mitogenome is 16, 367 bp in length with the structural organization of a typical bovine mitochondrial arrangement comprising 13 protein-coding genes, 21 tRNAs, and 2 rRNAs. No internal stop codon was found in the protein-coding genes. Phylogenetic tree analysis revealed that Malayan gaur is more closely related to Burmese banteng instead of gaur.